Bromatological composition of beet, elephant grass and fishmeal - Cosmo, Bruno Marcos Nunes (2021)
Food consumed by humans and animals must contain information on characterization, productive monitoring and legalization standards. Among the areas with this focus, bromatology or science that studies food, performs analysis of the composition of food, generating results applied by industry and the like. In this context, the present work aimed to characterize the bromatological composition of samples of beet, elephant grass and fishmeal, in addition to detailing the procedures and framing them with the literature. For this purpose, the bromatological composition of the elements was quantified: moisture and ash (obtained in complementary works), ether extract, crude protein and neutral detergent fiber. For the ether extract, extraction was performed using ether in a Soxhlet extractor. For crude protein, indirect determination was carried out through the determination of nitrogen by the Kjeldahl method. Finally, in determining neutral detergent fiber, a procedure with the same name was used. As a result, all samples were determined and categorized in percentage in relation to the sample's natural matter (considering humidity) and in relation to the sample's dry matter (disregarding humidity). For all elements and samples, the values are within the ranges obtained in the literature, with the exception of the neutral detergent fiber for fishmeal, which was above the literary value, due to the possible formation of fouling during the analysis. As considerations the study allowed to characterize the samples, in addition to detailing the procedures used for this and to discuss their importance, demonstrating the applications of this information in the planning of agro-industrial activities